ANALYSIS OF THE CUTTING BLADE FOR HDPE AND PET PLASTIC BOTTLE SHREDDERS FOR 3D PRINTING FILAMENT EXTRUSION - Adhiharto, Riky; Mandayusdi , Cahya Ramdan Putra; Rahmi, Meri (Jurnal Rekayasa Mesin, 2025)
The increasing use of filaments for 3D printing encourages the use of suitable plastic waste as a raw material for filaments. In Indonesia, plastic waste will reach 26.2 million tons in 2023, with 18.47% of it being plastic. To process plastic waste such as PET (Polyethylene Terephthalate) and HDPE (High Density Polyethylene) into filaments, maximum size of shredding is 2 mm. This study aims to design a plastic shredding machine using the VDI 2222 (Verein Deutscher Ingenieure) method. This machine is powered by an AC electric motor that rotates a pulley to drive the blade, using a shredder and granulator cutting type. This machine is expected to be able to shred PET and HDPE plastic with a thickness of 0.3–2 mm. The results of the study are in the form of a plastic shredding machine design with dimensions of 1682 x 898 x 791 mm.